Combining Cisplatin with Different Radiation Qualities-Interpretation of Cytotoxic Effects In Vitro by Isobolographic Analysis - Roswitha Runge; Falco Reissig; Nora Herzog; Liane Oehme; Claudia Brogsitter; Joerg Kotzerke (MDPI AG, 2023)
Background: The combination of platinum-containing cytostatic drugs with different radiation qualities has been studied for years. Despite their massive side effects, these drugs still belong to the therapeutic portfolio in cancer treatment. To overcome the disadvantages of cisplatin, our study investigated the cytotoxic effects of combining radionuclides with cisplatin. Methods: FaDu cells were treated with cisplatin (concentration ≈ 2 µM) and additionally irradiated after two hours with the alpha-emitter 223Ra, the beta-emitter 188Re as well as external X-rays using dose ranges of 2-6 Gy. Cell survival was followed by colony formation assays and plotted against cisplatin concentration and radiation dose. The results were interpreted by isobolograms. Results: Isobolographic analyses revealed a supra-additive cytotoxic effect for the combination of cisplatin and 223Ra. A sub-additive effect was observed for the combination of cisplatin and 188Re, whereas a protective effect was found for the combination with X-rays. Conclusions: The combination of cisplatin and 223Ra may have the potential to create a successfully working therapy scheme for various therapy approaches, whereas the combination with 188Re as well as single-dose X-ray treatment did not lead to a detectable radiosensitizing effect. Thus, the combination with alpha-emitters might be advantageous and, therefore, should be followed in future studies when combined with cytostatic drugs.